The Development of a Postgraduate Developmental Psychology Program with Islamic Orientation: IIUM Experience - Borhan, Lihanna; Janon, Nazariah Shar'ie; Alias, Intan Aidura; Nawawi, Junita; Dzulkifli, Mariam Adawiah; Mohd Noor, Noraini (2011)
With the advancement in the field of psychology, and the increasing need to look at issues at all levels of human development, a specialised post-graduate program in psychology is a timely offering for a university dedicated to be the innovator in higher education. This paper will present the curriculum and conceptual rationale of the new Masters in Developmental Psychology program. Although not meant to exclusively cater to the needs of the Muslim, the program is infused with Islamic orientation, and discussions will then focus on how this is woven throughout the curriculum.